Higher levels of systemic immune-inflammatory index are associated with the prevalence of gallstones in people under 50 years of age in the United States: a cross-sectional analysis based on NHANES - Meng, Chunli; Liu, Kai (Frontiers in Medicine, 2024)
Inflammation plays a significant role in gallstones formation.The prognosis of various illnesses was initially predicted using the systemic immune-inflammatory ind ex (SII). We performed an updated analysis on the impact of SII and gallstones.To investigate the connection between the SII and gallstones occurrence in a sample of individuals from the National Health and Nutrition Examination Survey (NHANES) database from 2017 to 2020, we employed logistic regression analysis, subgroup analysis, and smoothing curve fitting.In our study, an aggregate of 4,950 individuals over the age of 20 were enrolled, and 429 of them claimed to have gallstones. A fully adjusted model showed that the third and fourth quartiles of SII was parallel associated with gallstones in adults(OR=2.43,95% CI=1. OR=2.97, under 50 years. Subgroup analysis and smoothed curve fitting provided evidence in favor of this finding.According to our research, gallstones are more likely to occur in US adults younger than 50 years.